2020
DOI: 10.1021/jacs.9b11552
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of Anion−π Interaction in Aqueous Solution

Abstract: Noncovalent interactions play a constitutive role in numerous biological processes, including biomolecular adhesion, recognition, and transport. Unlike π−π and cation−π interactions, anion−π interaction was only recently and computationally recognized to participate in biomolecular science. Here, we present the first experimental identification and direct quantification of the nanomechanics of anion−π interaction in aqueous solution by using a surface forces apparatus with complementary computational simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…The normal force-distance profiles and adhesion forces between two components (namely cationic polypeptide and anionic surfactant) that form the bio-glue were determined using an SFA. The typical experimental setup and working principle of SFA have been reported previously 45 48 . Briefly, thin back-silvered mica sheets (thickness 1–5 μm) were first glued onto cylindrical silica disks (radius R = 2 cm).…”
Section: Methodsmentioning
confidence: 99%
“…The normal force-distance profiles and adhesion forces between two components (namely cationic polypeptide and anionic surfactant) that form the bio-glue were determined using an SFA. The typical experimental setup and working principle of SFA have been reported previously 45 48 . Briefly, thin back-silvered mica sheets (thickness 1–5 μm) were first glued onto cylindrical silica disks (radius R = 2 cm).…”
Section: Methodsmentioning
confidence: 99%
“…This is a remarkable result of direct observation of anion-p interactions with the force measurement, as reported by Zeng. 22 The effect of anion species on the inhibition was examined using 10 mM TBACl, TBABr, and TBAI in water (Fig. 5b-d).…”
Section: àmentioning
confidence: 99%
“…17,18 Furthermore, Zeng et al revealed that anion-p and cation-p interactions coexist during bioadhesion based on catecholic moieties with phosphate ester and potassium. 19 These reports reveal that anion-p interaction is an excellent tool to control not only small molecular functions but also macromolecular and macroscale phenomena at the material interfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zuschriften 16516 www.angewandte.de negatively charged. [18] Furthermore, Fujita et al, reported efficient guest capture in crystal sponges with electrondeficient triazine as their frameworks. [19] Hence, it is clear that anion-p interactions can be utilized for the selection of substrates for the photocatalytic reactions of GCNs and could further expand the scope and possibility of GCNs as photocatalysts.…”
Section: Angewandte Chemiementioning
confidence: 99%